Micellized Naringenin Augments Hemodynamics After Myocardial Infarction by Suppressing Tubulin Detyrosination - Noah Weingarten; Amit Iyengar; Jessica Dominic; Danika Meldrum; Andrew Belec; Sara Guevara-Plunkett; Rachel Wilson; Joyce Ho; Mrinal Patel; Chaitanya Karimanasseri; Ahmad Amirshaghaghi; Daphne Nie; et al. (Applied Sciences)
Impaired contractility after myocardial infarction (MI) causes cardiogenic shock. MARK4 activity impairs contractility post-MI by increasing α-tubulin detyrosination. We assessed the impact of naringenin, a small-molecule MARK4 inhibitor, on contractility post-MI. Naringenin (Nar) was encapsulated in PEG-PCL to augment bioavailability. Wistar rats were randomized to receive either MI + micellized naringenin (0.3 mg/kg) [MI-NarMic], MI + naringenin (0.3 mg/kg) in 1% DMSO [MI-NarDMSO], MI + empty micelle [MI-Mic], MI alone [MI-Untreated], or no MI [Sham]. MI was induced via left anterior descending artery ligation. Invasive hemodynamics with pressure–volume catheterization, cardiomyocyte contractility, and ventricular protein abundance were assessed one day post-MI. A total of 45 rats underwent hemodynamic assessment. MI-NarMic rats demonstrated decreased α-tubulin detyrosination relative to MI-Untreated rats (p < 0.05). Myocytes isolated from peri-infarct tissue had increased contraction and relaxation velocities in MI-NarMic versus MI-Untreated rats (both p < 0.0001). MI-NarMic rats had higher ejection fractions than MI-Mic and MI-Untreated rats (63 ± 3% v. 48 ± 5% vs. 39 ± 4%, p < 0.05) and similar levels to Sham (61 ± 1%, p = 0.97) and MI-NarDMSO (54 ± 5%) rats (p > 0.05). MI-Nar rats had greater stroke work and lower end-diastolic pressure and tau than MI-Untreated rats (all p < 0.05). Micellized naringenin is a translatable agent with the potential to rescue hemodynamics post-MI by inhibiting MARK4 and mitigating myocardial α-tubulin detyrosination.